Ms. Marvel. Stretched thin - Shammas, Nadia (Graphix, an imprint of Scholastic, 2021)
"Kamala Khan (a.k.a Ms. Marvel) is stretched too thin--literally. She's having a hard time balancing schoolwork with being a good friend, being there for her family, becoming the best fanfic writer this side of the Hudson River--and, you know, becoming a Super Hero. She's tired and just barely keeping control, BUT she's handling it. Totally. When a mysterious robot tries to infiltrate Avengers Tower, it'll be up to Ms. Marvel to (again, literally) pull herself together, learn to ask for help, and fix the mess she's made before anyone gets hurt!"--Back cover.